Performance review of high-quality-factor, low-noise, and wideband radio-frequency LC-VCO for wireless communication - Moghavvemi, M.; Attaran, A. (IEEE, 2011)
An extensive review of various integrated CMOSbased LC-VCO topologies with different configurations were presented in this article. This comparison sought to categorize suitable applications of each LCVCO topology. To this end, the discussion on phase noise reduction techniques in CMOS-based LC resonators for up-conversion was presented, followed by the study of the tail current and its effectiveness on LC resonator performance. Finally, the 1/f flicker noise contribution of active devices was analyzed based on CMOS technology.